Cytokine profiles and CD8+ T cells in the occurrence of acute and chronic hepatitis B - Xie, Si; Yang, Liu; Bi, Xiaoyue; Deng, Wen; Jiang, Tingting; Lin, Yanjie; Wang, Shiyu; Zhang, Lu; Liu, Ruyu; Chang, Min; Wu, Shuling; Gao, Yuanjiao; et al. (Frontiers in Immunology, 2022)
Objective We explore the expression of functional molecules on CD8+ T lymphocytes, cytokines concentration, and their correlation to occurrence of hepatitis B and hepatitis B virus (HBV) desoxyribose nucleic acid (DNA), hepatitis B surface antigen (HBsAg), hepatitis B envelope antigen (HBeAg), and alanine aminotransferase (ALT) in patients infected with HBV. Methods This is a single center study. 32 patients with acute hepatitis B (AHB), 30 patients with immune tolerant (IT) phase chronic HBV infected, and 50 patients with chronic hepatitis B (CHB) were enrolled. The activation molecules (CD69) and the apoptosis-inducing molecules (CD178) on surface of CD8+ T lymphocytes were tested by the flow cytometry. Fms-like tyrosine kinase 3 ligand (Flt-3L), interleukin 17A (IL-17A), interferon γ (IFN-γ), and Interferon α2 (IFN-α2) were quantitated by Luminex assay. We use linear regression analysis to analyze their correlations to ALT, HBV DNA, HBsAg, and HBeAg. Results The frequency of CD69+CD8+ T lymphocytes in CHB and AHB groups were increased significantly compared with IT group (4.19[3.01, 6.18]% and 4.45[2.93, 6.71]% vs. 3.02[2.17, 3.44]%; H=26.207, P=0.001; H=28.585, P=0.002), and the mean fluorescence intensity (MFI) of CD69 in AHB group was significantly higher than IT and CHB groups (27.35[24.88, 32.25] vs. 20.45[19.05, 27.75] and 23.40[16.78, 28.13]; H=25.832, P=0.005 and H=22.056, P=0.008). In IT group, HBsAg levels and HBV DNA loads were negatively correlated with CD69MFI (β=-0.025, t=-2.613, P=0.014; β=-0.021, t=-2.286, P=0.030), meanwhile, HBeAg was negatively related to the frequency of CD69+CD8+ T lymphocytes (β=-61.306, t=-2.116, P=0.043). In AHB group, IFN-α2 was positively related to the frequency of CD8+ T lymphocytes (β=6.798, t=2.629, P=0.016); however, in CHB group, IFN-α2 was negatively associated with frequency of CD8+ T lymphocytes (β=-14.534, t=-2.085, P=0.043). In CHB group, HBeAg was positively associated with frequency of CD69+CD8+ T lymphocytes (β=43.912, t=2.027, P=0.048). In AHB group, ALT was positively related to CD69MFI (β=35.042, t=2.896, P=0.007), but HBsAg was negatively related to CD178MFI (β=-0.137, t=-3.273, P=0.003). Conclusions The activation of CD8+ T lymphocytes was associated with the occurrence of AHB and CHB. However, due to the insufficient expression of functional molecules of CD8+ T lymphocytes and the depletion of CD8+ T lymphocytes, CHB patients were difficult to recover from HBV infection.